Description of Nurses' Knowledge and Experience In the Accuracy of Giving Triage Labels in the Emergency Room Tajuddin Khalid Hospital, City of Makassar - Achmad, Viyan Septiyana; Rosida, Rosida; Rahmat, Rezqiqah Aulia; Apriani, Baiq Nurainun; Saputra, M. Khalid Fredy (International Journal of Health Sciences, 2024)
Victims with an emergency condition are a condition that can be life threatening and the patient needs immediate help. If treatment is not provided quickly and appropriately, the patient will experience disability or death. The characteristics of emergency room patients are patients who experience an emergency in terms of disruption of the airway, respiratory function, circulatory function, brain function and consciousness and patients who suffer from sudden illness (rapid onset). This condition requires immediate help if treatment is not carried out immediately. causing increased pain in the victim. The aim of this study is to determine the description of nurses' knowledge and experience regarding the accuracy of giving triage labels in hospitals. This research method the type of research used in this research is analytical descriptive with a cross sectional approach. The population in this study were emergency room nurses at Tajuddin Chalid Hospital. The sampling technique used was total sampling. With a total sample size of 25 respondents. The research instrument uses questionnaire questions as an interview guide and observation sheet to collect all data which is analyzed using SPSS. The results of this study explain that the most common characteristics for age were 14 respondents and for gender there were 19 respondents. The results of the bivariate test using the Spearman correlation test were obtained (p=value) = 0.000, which is smaller than the value α=0.05. Conclusion Work experience does not always influence nurses' knowledge about the accuracy of giving triage labels in the Emergency Room. However, there is a relationship between nurses' knowledge about triage labels and nurses' actions based on triage labels at Tajuddin Chalid Hospital.